2000
DOI: 10.1097/00002030-200011100-00016
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for postnatal mother–child transmission of HIV-1

Abstract: In addition perinatal antiretroviral therapies, public health strategies should address: (i) prevention of maternal nipple lesions, mastitis and infant thrush; (ii) reduction of breastfeeding duration by all HIV-1-infected mothers; (iii) absolute avoidance of breastfeeding by those at high risk, and (iv) prevention of HIV-1 transmission to breastfeeding mothers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
1
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(94 citation statements)
references
References 49 publications
7
84
1
2
Order By: Relevance
“…The difference of the result may be due to, PMTCT services are recently integrated to ANC service and the service is being strengthened from time to time [21][22][23][24]. A large proportion of study subjects (91.1%) were aware of infant feeding option of HIV positive mothers which is in concordance with the study conducted in Addis Ababa, Gurage zone, which confirmed most respondents around 80% were aware of the recommended feeding option of infants below six months old born from HIV positive women [20,23].…”
Section: Variablessupporting
confidence: 73%
See 1 more Smart Citation
“…The difference of the result may be due to, PMTCT services are recently integrated to ANC service and the service is being strengthened from time to time [21][22][23][24]. A large proportion of study subjects (91.1%) were aware of infant feeding option of HIV positive mothers which is in concordance with the study conducted in Addis Ababa, Gurage zone, which confirmed most respondents around 80% were aware of the recommended feeding option of infants below six months old born from HIV positive women [20,23].…”
Section: Variablessupporting
confidence: 73%
“…This may be due to small number of HIV positive samples and methodological differences even though the finding is similar from South Africa findings. The median age of infants during HIV test in this study was 3 months [18][19][20].…”
Section: Variablesmentioning
confidence: 99%
“…Breast milk viral load is an important determinant of postnatal HIV transmission [3,[10][11][12][13] and is associated with high plasma viral load [14,15], advanced HIV disease [16,17], and mastitis [7,10]. Increases in mammary epithelial permeability which accompanies weaning in animals [18,19] and humans [20,21] may also increase breast milk viral load.…”
Section: Discussionmentioning
confidence: 99%
“…HIV 2 lower risk control women (HIV 2 LR) (n = 20) with no history of sex work and only one sexual partner for the last 6 mo before this study were recruited through a Maternal Health Clinic based at the Pumwani Maternity Hospital (25,26). General inclusion criteria were age at least 18 y, uterus and cervix present, not actively menstruating, no symptomatic or clinically apparent cervical inflammation, willingness to undergo ectocervical biopsy collection, and to abstain from vaginal sex during a healing period of 2 wk.…”
Section: Study Populations and Proceduresmentioning
confidence: 99%